Electrochemical Sensing Platform Based on Renewable Carbon Modified with Antimony Nanoparticles for Methylparaben Detection in Personal Care Products - Gomes, Gabriela Contesa [UNESP]; da Silva, Martin Kássio Leme [UNESP]; Barreto, Francisco Contini [UNESP]; Cesarino, Ivana [UNESP] (MDPI, 2023)
This paper describes for the first time the surface modification of glassy carbon (GC) electrodes with bamboo-based renewable carbon (RC) and antimony nanoparticles (SbNPs) for the determination of methylparaben (MePa) in personal care products (PCPs). The synthesized RC-SbNP material was successfully characterized by scanning electron microcopy, energy-dispersive X-ray spectroscopy and cyclic voltammetry. The proposed sensor was applied in the detection of MePa using the optimized parameters by differential pulse voltammetry (DPV). The analytical range for detection of MePa was 0.2 to 9.0 µmol L−1, with limits of detection and quantification of 0.05 µmol L−1 and 0.16 µmol L−1, respectively. The determination of MePa in real PCP samples was performed using the proposed GC/RC-SbNP sensor by DPV and UV-vis spectrophotometry as comparative methodology. The use of RC-SbNP material for the development of electrochemical sensors brings a fresh approach to low-cost devices for MePa analysis.
Keywords: antimony nanoparticles; electrochemical sensors; methylparaben; personal care products; renewable carbon